DISTRIBUTION OF KARNAL BUNT OF WHEAT IN PAKISTAN (Biological Sciences - PJSIR, 2022)
A total of 2274 wheat seed samples were tested for Kamal bunt incidence during 1986-87 to 1991-92 by dry inspectionmethod. Out of these, 1331 (58.53%) samples were found infected by Kamal bunt fungus (Tilletia indica). Thehighest infection percentage of Kamal bunt was found in Central Punjab (7.66%) and North West area of Pakistan(8.72%). On the basis of sample infection percentage, Rahim Yar Khan, Sukkur, Sakrand, Hyderabad and Quetta werethe most suitable areas for the production of disease free quality seed. Comprehensive review regarding Kamal bunt investigationalongwith suggestions is given for planning effective disease management strategy. As the fungus hasquarantine significance, domestic and international measures should be adopted to check its further spread.